Retraction Notice for “A Chronicle Overview of Cephalometric Parameters for assessing Sagittal Jaw Disparity.” (Orthodontic Journal of Nepal, 2025)
Retraction Notice for “A Chronicle Overview of Cephalometric Parameters for assessing Sagittal Jaw Disparity.”Authors: Dr. Jaina Dubey, Dr. Amitabh Kallury, Dr. Rajesh Kumar Balani, Dr. Chandni Bharti, Dr. Chandrika DubeyThe Editorial Board of the Orthodontic Journal of Nepal agreed to retract the article “A Chronicle Overview of Cephalometric Parameters for assessing Sagittal Jaw Disparity” published in the Orthodontic Journal of Nepal 2021, Volume 11, Number 2, pp. 72-79.1 (https://doi.org/10.3126/ojn.v11i2.43282).It has been found that the manuscript contains inadvertent textual overlap and unintended similarity to an article previously published by Dr. Vinay Kumar and Dr. Shobha Sundareswaran in the Journal of the Indian Orthodontic Society (JIOS) in 2014.2 (https://journals.sagepub.com/doi/pdf/10.5005/jp-journals-10021-1215).After careful evaluation and in the interest of maintaining the highest standards of academic integrity, publication ethics, and transparency, the Orthodontic Journal of Nepal retracts this manuscript.References• Dubey J, Kallury A, Balani RK, Bharti C, Dubey C. A Chronicle Overview of Cephalometric Parameters for assessing Sagittal Jaw Disparity. Orthod J Nepal. 2021 Dec.;11(2):72-9.• Kumar V, Sundareswaran S. Cephalometric Assessment of Sagittal Dysplasia: A Review of Twenty-One Methods. J Ind Orthod Soc 2014;48(1):33-41.